2023
DOI: 10.5847/wjem.j.1920-8642.2023.066
|View full text |Cite
|
Sign up to set email alerts
|

Unmanned aerial vehicle based intelligent triage system in mass-casualty incidents using 5G and artificial intelligence

Abstract: BACKGROUND: Rapid on-site triage is critical after mass-casualty incidents (MCIs) and other mass injury events. Unmanned aerial vehicles (UAVs) have been used in MCIs to search and rescue wounded individuals, but they mainly depend on the UAV operator's experience. We used UAVs and artificial intelligence (AI) to provide a new technique for the triage of MCIs and more efficient solutions for emergency rescue. METHODS:This was a preliminary experimental study. We developed an intelligent triage system based on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…They developed an intelligent triage system based on two AI algorithms, namely OpenPose and YOLO. They concluded that the proposed technique may provide an alternative technique for the triage of MCIs, and it is an innovative method in emergency rescue 31 …”
Section: Discussionmentioning
confidence: 99%
“…They developed an intelligent triage system based on two AI algorithms, namely OpenPose and YOLO. They concluded that the proposed technique may provide an alternative technique for the triage of MCIs, and it is an innovative method in emergency rescue 31 …”
Section: Discussionmentioning
confidence: 99%
“…Although 'Search & Rescue' is not explicitly 'Health Care Delivery', it was featured as a topic within healthcare delivery manuscripts. These topics relate to autonomous control systems, GPS, and smart detection devices, presumably improving search operations in diverse environments and situations [39,43,44]. This research aimed to develop techniques that enable UAVs to locate and assist patients swiftly and accurately, often in challenging or hazardous terrain.…”
Section: Drones In the Delivery Of Time-critical Medical Itemsmentioning
confidence: 99%